Erratum: Analisis Pengetahuan dan Partisipasi Siswa Sekolah Dasar Terhadap Permainan Tradisional - Gustiana Mega Anggita; Mohammad Arif Ali; Sugiarto Sugiarto; Siti Baitul Mukarromah (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v5i1.769 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.